2016
DOI: 10.1590/1518-8345.1205.2786
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors and health conditions associated with the resilience of people with chronic diseases: a cross sectional study

Abstract: Objective: to investigate the association between resilience and sociodemographic variables and the health of people with chronic kidney disease and / or type 2 diabetes mellitus. Method: a cross-sectional observational study performed with 603 people with chronic kidney disease and / or type 2 diabetes mellitus. A tool to collect socio-demographic and health data and the Resilience Scale developed by Connor and Davidson were applied. A descriptive and multivariate analysis was performed. Results: the study pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0
26

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 18 publications
5
31
0
26
Order By: Relevance
“…It was observed that the majority of the elderly presented moderate levels of resilience, which could be related to the typical characteristics of this population, the time of living with the disease, and the acceptance of the difficulties resulting from diabetes mellitus. Overcoming obstacles can provide the necessary support to deal with the adversities inherent to this morbidity, favoring the adaptation to changes to maintain glycemic stability (2,6) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was observed that the majority of the elderly presented moderate levels of resilience, which could be related to the typical characteristics of this population, the time of living with the disease, and the acceptance of the difficulties resulting from diabetes mellitus. Overcoming obstacles can provide the necessary support to deal with the adversities inherent to this morbidity, favoring the adaptation to changes to maintain glycemic stability (2,6) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that when elderly people face hostile situations, they tend to prioritize pleasurable experiences and minimize conflicts, because the burden of life experience becomes a determining factor for adjustment and overcoming of difficult circumstances experienced by this population (4,6) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it features a false adaptation to the experienced situation concealing fear, resulting or aggravating the suffering. We must promote resilience, which, unlike conformity, indicates the positive adaptation and active acceptance of the disease condition, enabling the development of inner coping capabilities (23)(24) .…”
Section: Discussionmentioning
confidence: 99%